(xz+yz)dz/dy + (xz-yz)dz/dy = x2+y2 find the general solution
"(xz(y)+yz(y))z'(y)+(xz(y) - yz(y))z'(y)=x^2+y^2"
Ordinary differential equation classification:
first order nonlinear ordinary differential equation
"\\frac{\\large dz(y)}{\\large dy}(xz(y)-yz(y))+\\frac{\\large dz(y)}{\\large dy}(xz(y)+yz(y))=x^2+y^2"
Solve for "\\frac{\\large dz(y)}{\\large dy}"
"\\space\\space\\frac{\\large dz(y)}{\\large dy} = \\frac{\\large x^2+y^2}{\\large 2xz(y)}"
Multiply both sides by "2xz(y):"
"2x\\frac{\\large dz(y)}{\\large dy}z(y)=x^2+y^2"
Integrate both sides with respect to y:
"\\int 2x\\frac{\\large dz(y)}{\\large dy}z(y)dy=\\int (x^2+y^2)dy"
Evaluate the integrals:
"xz(y)^2 = \\frac{\\large y^3}{\\large 3}+x^2y+C_1." where "C_1" is an arbitrary constant.
Solve for z(y):
"Answer: \\space z(y) = - \\large\\frac{\\sqrt{y^3+3x^2y+3C_1}}{\\sqrt{3x}} \\space or \\space \\large\\frac{\\sqrt{y^3+3x^2y+3C_1}}{\\sqrt{3x}}"
Comments
Leave a comment